AVICENNIA OBSERVATION FIELD GUIDE IN MANGROVE AREA, SUNGAI RASAU, INDONESIA - Ahadina Husnul Mawadah; Mahrudin Mahrudin; M. Arsyad (Universitas Negeri Padang, 2022)
Local potential can be utilized in biology learning, especially to increase students' knowledge. This kind of learning is called contextual. The subject